Detection of haplosporidian protistan parasites supports an increase to their known diversity, geographic range and bivalve host specificity. Issue 5 (15th April 2020) - Lynch, S. A.; Lepée-Rivero, S.; Kelly, R.; Quinn, E.; Coghlan, A.; Bookelaar, B.; Morgan, E.; Finarelli, J. A.; Carlsson, J.; Culloty, S. C.
Abstract: Haplosporidian protist parasites are a major concern for aquatic animal health, as they have been responsible for some of the most significant marine epizootics on record. Despite their impact on food security, aquaculture and ecosystem health, characterizing haplosporidian diversity, distributions and host range remains challenging. In this study, water filtering bivalve species, cockles Cerastoderma edule, mussels Mytilus spp. and Pacific oysters Crassostrea gigas, were screened using molecular genetic assays using deoxyribonucleic acid (DNA) markers for the Haplosporidia small subunit ribosomal deoxyribonucleic acid region. Two Haplosporidia species, both belonging to the Minchinia clade, were detected in C. edule and in the blue mussel Mytilus edulis in a new geographic range for the first time. No haplosporidians were detected in the C. gigas, Mediterranean mussel Mytilus galloprovincialis or Mytilus hybrids. These findings indicate that host selection and partitioning are occurring amongst cohabiting bivalve species. The detection of these Haplosporidia spp. raises questions as to whether they were always present, were introduced unintentionally via aquaculture and or shipping or were naturally introduced via water currents. These findings support an increase in the known diversity of a significant parasite group and highlight that parasite species may be present in marine environments but remain undetected, even in well-studied host species.